THE EFFECT OF MONDAY THURSDAY FAST HABITS ON GLUCOSE, CHOLESTEROL, AND URIC ACID IN YOUNG ADULT WOMEN - Nurul Marfu'ah; Zulianita Zulianita; Amal Fadholah; Khomarul Kuniyati; Sujiat Zubaidi (International Islamic Medicine Forum, 2022)
Excess levels of glucose, cholesterol, and uric acid can cause health problems called hyperglycemia, hypercholesterolemia, and hyperuricemia. It is better to take preventive measures than to treat patients who have been exposed to the disease. One of the preventive measures is to fast on Mondays and Thursdays when they are still younger. By fasting, food intake will be controlled so that hyperglycemia, hypercholesterolemia, and hyperuricemia can be avoided. Based on this background, this study aims to determine the effect of sunnah fasting on Mondays and Thursdays on glucose, cholesterol, and uric acid levels in young adult women. This study is an experimental study with two treatment groups, namely the group that is accustomed to fasting sunnah Monday and Thursday for 6-12 months and the group that is not accustomed to fasting as a control. The research subjects were 40 students of University of Darussalam Gontor Female, Mantingan Campus, Ngawi, East Java which were divided into 2 treatment groups. Research subjects have an age range of 19-23 years, weight 40-65 kg, and height 145-165 cm. Measurement of glucose, cholesterol and uric acid levels was carried out once on research subjects using the Easy Touch GCU tool. Analysis of the data used is the Independent-T Test with a significance level of 95% using the SPSS 16.0 statistical program. The results showed that blood glucose levels in the group of young women who were accustomed to fasting were lower than the control group (young women who were not accustomed to fasting). Meanwhile, cholesterol and uric acid levels in the group of young women who were accustomed to fasting were higher than the control group (young women who were not accustomed to fasting). Although this difference was not statistically significant (p > 0.05).